Investigation of phase-separated electronic states in 1.5 µm GaInNAs/GaAs heterostructures by optical spectroscopy - Sun, Handong (2009)
We report on the comparative electronic state characteristics of particular GalnNAs/GaAs quantum well structures that emit near 1.3 and 1.5 μm wavelength at room temperature. While the electronic structure of the 1.3 μm sample is consistent with a standard quantum well, the 1.5 μm sample demonstrate quite different characteristics. By using photoluminescence (PL) excitation spectroscopy at various detection wavelengths, we demonstrate that the macroscopic electronic states in the 1.5 μm structures originate from phase-separated quantum dots instead of quantum wells. PL measurements with spectrally selective excitation provide further evidence for the existence of composition-separated phases. The evidence is consistent with phase segregation during the growth leading to two phases, one with high In and N content which accounts for the efficient low energy 1.5 μm emission, and the other one having lower In and N content which contributes metastable states and only emits under excitation in a particular wavelength range.